Challenging word games - Allem, Mayme (Sterling Publishing, 1997)
Words you can use every day can drive you crazy, not once, but dozens of times, with these fun games that turn letters and phrases into tricky puzzles. Try all ten types to find different ways to show off your problem-solving genius. When you brain needs a break there are lively cartoons to entertain you.